Korelasi Rasio Neutrofil Limfosit dengan Lama Rawat Inap - Diah Ayu Wikan Nastiti; Wiwit Agung Sri Nur Cahyawati; Roselina Panghiyangani (Homeostasis, 2022)
Abstrack: Systemic inflammation can be characterized by an increased NLR. Systemic inflammation induce physiological changes, vulnerability, and even death. Elderly often experience various health complaints that cause prolonged hospitalization. Increased NLR is clinical marker that can be a preventive measure to predict length of stay. This study aims to analize correlation of NLR and length of stay of elderly. An analytical observasional with cross-sectional method using secondary data from medical records at RSUD Ulin Banjarmasin period July-November 2021. Total 44 samples using total sampling technique. Data analysis used non-parametric correlation Spearman. Median NLR 7.7 (1,3-73,3). Median length of stay 5.5 (1-16) days, average age of the elderly 66±4.65 years. There is a significant relationship between NLR and length of stay with a weak correlation and positive direction (r=0.392; p=0.008). The conclution is there is a relationship between NLR and length of stay of elderly in Internal Room at RSUD Ulin Banjarmasin. Keywords: elderly, neutrophil lymphocyte ratio, length of stay. Abstrak: Inflamasi sistemik dapat ditandai dengan peningkatan RNL Inflamasi sistemik mengakibatkan perubahan fisiologis tubuh, kerentanan, bahkan kematian. Lansia sering mengalami berbagai keluhan yang menyebabkan rawat inap memanjang. Peningkatan RNL merupakan penanda klinis yang dapat menjadi upaya preventif untuk memprediksi lama rawat. Penelitian ini bertujuan menganalisis korelasi RNL dengan lama rawat inap pasien lansia. Penelitian observasional analitik dengan metode cross-sectional menggunakan data sekunder rekam medik RSUD Ulin Banjarmasin periode Juli-November 2021. Sampel sejumlah 44 menggunakan teknik total sampling. Analisis data menggunakan uji korelasi non-parametrik Spearman. Median RNL 7,7 (1,3-73,3). Median lama rawat inap 5,5 (1-16) hari, rerata umur lansia 66±4,65 tahun. Terdapat hubungan bermakna antara RNL terhadap lama rawat inap berupa korelasi lemah serta arah hubungan positif (r=0,392; p=0.008). Kesimpulan terdapat hubungan antara RNL dengan lama rawat inap pasien lansia di Ruang Rawat Penyakit Dalam RSUD Ulin Banjarmasin. Kata-kata kunci: lansia, rasio neutrofil limfosit, lama rawat inap.